Acceptance of Open Preperitoneal Repair in Inguinal Hernia Surgery Delphi-Consensus After an Anonymous International Survey Among European Hernia Society Members - Lorenz, R (2025)
Introduction: For years, the Lichtenstein technique was the gold standard for open repair, but several open pre-peritoneal techniques have developed since the fifties of the 20th century that offer some benefits over the Lichtenstein technique in terms of post-surgical incidence of pain. Since the 2023 update of the International HerniaSurge Guidelines, open preperitoneal mesh techniques have been an acceptable alternative, providing available expertise and competence with at least equal results as Lichtenstein repair. Aim: The aim of this project is to understand the views of surgeons regarding the approach to inguinal hernia repair and determine best practice principles for optimal surgical outcomes. Methods: Using a modified Delphi method, a panel of experts developed 43 Likert scale statements across six key domains. These statements were used to develop an online survey distributed to surgeons in Europe involved in inguinal hernia repair. The threshold for consensus was set a priori at 75%. Results: A total of 202 responses were received from surgeons involved in inguinal hernia repair over three rounds of survey. After the initial survey round, seven statements were revised and reissued for a further round. At the conclusion of the survey phase, 31 of the 38 remaining statements achieved consensus (of which 13 achieved ≥90% agreement). From these results, the panellists developed a set of 3 recommendations to help define principles for optimal approach to inguinal hernia repair. Accordingly Open preperitoneal techniques seems to be an alternative to Lichtenstein technique if expertise is available and should be included in a tailored concept. Knowledge of anatomy, Education and Training in open preperitoneal techniques is crucial for the acceptance of these techniques. Conclusion: The proposed set of recommendations provides some principles for surgeons to consider when selecting an approach to inguinal hernia repair, ensuring good patient outcomes in a practical and cost-effective manner.